The Effectiveness of Guided Inquiry-Based Worksheets to Improve Students' Critical Thinking Skills on Archimedes’ Law Materials - Suci Rizki Lestari; Yanti Sofi Makiyah (Universitas Lambung Mangkurat, 2021)
This study aimed to determine the effectiveness of Guided Inquiry-based Student Worksheets on Archimedes’ Law. This study used an experimental method with a research design of one group pretest-posttest design. The population in this study was all students of class XI MIA Public Senior High School 1 Sariwangi, the research sample was XI MIA 2. The sampling technique was done by using cluster random sampling. The data collection instrument used a pretest and posttest assessment sheet. Data analysis used statistical tests, namely N-Gain and t-test. The test result of the effectiveness of student worksheets based on guided inquiry using N-Gain analysis obtained a value of 0.97 with high criteria. Furthermore, the result of the t-test showed 15tcount>t(0,995)(30)